Pemanfaatan Limbah Industri Baja sebagai Bahan Baku Pembuatan Logam Pig Iron : Peleburan Mill Scale Menggunakan Submerged Arc Furnace [Utilization of Steel Making Industrial Waste to Produce Pig Iron: Smelting Process of Mill Scale Using Submerged Arc...] - Nurjaman, Fajar; Prilitasari, Nurbaity Marsas; Prasetyo, Arif Eko; Nugroho, Eko (Jurnal Metalurgi, 2019)
Mill scale is a by-product that resulted from the steel making industries containing iron oxides, such as hematite (Fe2O3), magnetite (Fe3O4) and wustite (FeO). The smelting process of mill scale into pig iron as secondary raw material for the steel making process has conducted. A 30 Kg of mill scale which crushed into -40 mesh, 0-6 kg amount of coal (internal reductant) and 2 wt.% (0.6 kg) of bentonite (binder) were mixed homogeneously and agglomerated using briquette machine. The composite briquette had been smelting together with 7-8 kg of coke (external reductant) and 0-4.5 kg of limestone (flux) using submerged arc furnace. The smelting process was carried out for 45 minutes, and the pouring temperature was 1450-1500 ºC. The study of coal addition in composite briquette, amount of cokes and limestone addition in the smelting process of mill scale has been investigated clearly. The optimum specified consumption energy of smelting process of mill scale was 3.64 kWh/kg product, resulted from the smelting of 30 kg of mill scale with 0% coal addition in composite briquette together with 3 kg (10 wt.%) lime stones and 7 kg of cokes (stoichiometric) addition. The optimum basicity for smelting a mill scale was 1.0. The pig iron which resulted from smelting the mill scale could promote as a raw material for producing grey cast iron, white cast iron, and malleable cast iron.